Improving fast-ion confinement in high-performance discharges by suppressing Alfvén eigenmodes. (28th March 2017) - Kramer, G.J.; Podestà, M.; Holcomb, C.; Cui, L.; Gorelenkov, N.N.; Grierson, B.; Heidbrink, W.W.; Nazikian, R.; Solomon, W.; Van Zeeland, M.A.; Zhu, Y.
Abstract: We show that the degradation of fast-ion confinement in steady-state DIII-D discharges is quantitatively consistent with predictions based on the effects of multiple unstable Alfvén eigenmodes on beam-ion transport. Simulation and experiment show that increasing the radius where the magnetic safety factor has its minimum is effective in minimizing beam-ion transport. This is favorable for achieving high performance steady-state operation in DIII-D and future reactors. A comparison between the experiments and a critical gradient model, in which only equilibrium profiles were used to predict the most unstable modes, show that in a number of cases this model reproduces the measured neutron rate well.